Agile Governance Implementation through the DOLEN Program to Boost Reading Interest in East Java - Fierda Nurany; Bagus Ananda Kurniawan; Annastya Putri Kirana (Soshum: Jurnal Sosial dan Humaniora)
This research was conducted with the aim of finding out the extent of the application of Agile Governance principles during the Covid-19 pandemic to the East Java Provincial Library and Archives Service through the launch of the Online Fairy Tale Program (DOLEN). The researcher uses a qualitative approach with a type of descriptive research. The researcher conducted a data analysis based on the Agile Governance theory proposed by Luna et al, (2015). The researcher focuses on 3 (three) principles of Agile Governance.